Age Hardening in Ultrafine-Grained Al-2 Pct Fe Alloy Processed by High-Pressure Torsion - Cubero-Sesin, Jorge; Horita, Zenji (Springer Boston, 2015)
A cast Al-2 wt pct Fe alloy was processed by high-pressure torsion (HPT) at room temperature and then subjected to artificial aging at temperatures of 373 K and 473 K (100 °C and 200 °C). The aging behavior was studied by Vickers microhardness measurements and by microstructural analyses using transmission electron microscopy and X-ray diffraction. The initial intermetallic structures, composed of a mixture of Al + Al6Fe and Al + Al3Fe eutectics phases, were partially dissolved in the matrix up to a supersaturation of ~1 wt pct Fe. The microstructure was refined by HPT to an ultrafine-grained level with a minimum grain size of ~120 nm in the matrix and a dispersion of particles less than 400 nm. Age hardening was achieved within 0.25 hours at 473 K (200 °C), to a maximum UTS of ~700 MPa as a result of nano-sized precipitation within the ultrafine grains. The uniform elongation exceeded ~12 pct even at intermediate levels of imposed strain by HPT, while it decreased to ~6 pct with the subsequent aging treatment. The thermal stability of the ultrafine-grained structure was verified to exceed 16 days at 373 K (100 °C) and 12 hours at 473 K (200 °C). © 2015, The Minerals, Metals & Materials Society and ASM International.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84937759515&partnerID=40&md5=6c6d7635f04f5ef9de34768fe585779c
Keywords: Aleaciones; Termodinámica; Hierro; Difracción; Torsiones; Rayos X; Research Subject Categories::TECHNOLOGY::Materials science::Other processing/assembly